Vascular Anatomy of the Spinal Cord and Classification of Spinal Arteriovenous Malformations - Miyasaka, K. (Centauro S.r.l., 2000)
The arterial and venous anatomy of the spinal cord was described in terms of extrinsic and intrinsic contribution to the cord substance. Based upon anatomical location of an arteriovenous shunt, spinal arteriovenous malformations (AVMs) were classified into intramedullary AVM, perimedullary arteriovenous fistula (AVF) and duralAVF. This simple classification seems practical from the standpoint of endovascular and surgical treatments since it reflects anatomical differences in the shunt location, which is the target in either approach.